Resistance and oppression towards the Catholic Church in Chile: 1973-1990 - Sampson, Elizabeth Abigail (2021)
The Pinochet regime lasted seventeen (17) years in Chile. During this period, the Catholic Church experienced many challenges with the dictator, Augusto Pinochet. It is notable that the multiple perspectives within the Catholic Church contributed to the challenges already faced by this religious organization. The Catholic Church was a counterculture and fought against religious oppression. This article highlights the various resistance methods by the Catholic Church (1973-1990).